Analisis Blue Ocean Strategy dalam Pengembangan Bakat dan Minat Siswa MI Syarifuddin Lumajang - Aminatuz Zahroh (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat - Islamic Institute of Syarifuddin Lumajang, Indonesia., 2021)
It is an inevitability if Islamic school must participate in the competition in some aspects of Islamic schooling. Such as curriculum, human resource development, public relations and so on. One of the extracurricular curricula is the development of talents and interests. Blue Ocean Strategy is one of the right strategies used to develop students' talents and interests. However, in reality the development of talents and interests sometimes find obstacles in their implementation, such as inadequate costs, so it cannot recruet the professional coach of talent and interest development activities. In addition, it is also caused by inadequate facilities and infrastructure so that the development of talents and interests can not run smoothly. Looking at the condition, the researchers gave a way out to solve the problem.